The prohibition of wearing veil in public schools in Egypt: an analysis of the Egyptian Supreme Constitutional Court jurisprudence - Arafa, Mohamed A. (Revista de Investigações Constitucionais, 2017)
Case No.8 of 1996 is a landmark decision of the Egyptian Supreme Constitutional Court (“SCC”) and represents one of the most significant judicial rulings of a structural remedy for the interpretation of Article 2 of Egypt 2014 Constitution. The jurisprudence of the SCC is essential to advance a moderate (liberal), rights-protecting interpretation of Sharie‘a. In this case, the SCC held that a rule on face-veiling in public schools is compatible not only with Islamic law, but with certain human rights guaranteed by the Constitution:, as freedom of expression and freedom of religion. This decision dealt with the SCC’s view on Islamic ijtihad (legal reasoning), and, gives insight into the Court’s views on civil and political rights context.